Screening for Asymptomatic Coronary Artery Disease via Exercise Stress Testing in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Dun, Yaoshan; Wu, Shaoping; Cui, Ni; Thomas, Randal J.; Olson, Thomas P.; Zhou, Nanjiang; Li, Qiuxia; Liu, Suixin (Frontiers in Cardiovascular Medicine, 2021)
Objectives: This meta-analysis aims to investigate the diagnostic value of exercise stress testing (EST) for asymptomatic coronary artery disease (CAD) among patients with type 2 diabetes mellitus (T2DM) and to ascertain the influence of different variables on the sensitivity and specificity of EST. Background: Asymptomatic CAD occurs in >1 in five diabetes mellitus patients, and it is associated with an increased risk of complications. Methods for screening asymptomatic CAD in T2DM patients are still not unified. Methods: MEDLINE (via Ovid), Embase (via Ovid), Cochrane Library, SCOPUS, PubMed, Ovid, EBSCO ASP, and Web of Science were systematically searched on June 8 and 9, 2021, for diagnostic cohort and case-control studies. We included studies that used EST to screen for CAD in asymptomatic patients with T2DM, and that used coronary angiography to diagnose CAD and had reported the basic diagnostic indicators. The Quality Assessment of Diagnostic Accuracy Studies 2 tool was used to assess study quality. The combined effect sizes were calculated by overall analysis and multiple variable effects were explored by regression analysis and subgroup analysis. Results: Nine groups of data from eight diagnostic cohort studies, totaling 515 participants, were included. Included studies showed a low risk of bias in most items, except for flow and timing. The combined sensitivity and specificity of EST for asymptomatic CAD in patients with T2DM were 55 (48 to 61%) and 66 (61 to 70%), respectively. When non-diagnostic tests were excluded, sensitivity increased to 73 (56 to 88%). The proportion receiving angiography also significantly affected sensitivity. No significant difference was found in the duration of diabetes or other additional risk factors. Conclusions: EST is a tool of moderate sensitivity and specificity to be used for the initial screening of asymptomatic CAD in T2DM. It has the advantage of being non-invasive, relatively inexpensive, easily available in most settings, and has no radiation associated with its use. Additional research with higher quality studies in which tests that are non-diagnostic are included and flow and timing is described clearly, will be important to further our understanding of EST for asymptomatic CAD detection in patients with T2DM. Systematic review registration: PROSPERO CRD42021259555.